Magnetic Nanoconjugated Teicoplanin: A Novel Tool for Bacterial Infection Site Targeting - Armenia, Ilaria; Marcone, Giorgia Letizia; Berini, Francesca; Orlandi, Viviana Teresa; Pirrone, Cristina; Martegani, Eleonora; Gornati, Rosalba; Bernardini, Giovanni; Marinelli, Flavia (Frontiers in Microbiology, 2018)
Nanoconjugated antibiotics can be regarded as next-generation drugs as they possess remarkable potential to overcome multidrug resistance in pathogenic bacteria. Iron oxide nanoparticles (IONPs) have been extensively used in the biomedical field because of their biocompatibility and magnetic properties. More recently, IONPs have been investigated as potential nanocarriers for antibiotics to be magnetically directed to/recovered from infection sites. Here, we conjugated the “last-resort” glycopeptide antibiotic teicoplanin to IONPs after surface functionalization with (3-aminopropyl) triethoxysilane (APTES). Classical microbiological methods and fluorescence and electron microscopy analysis were used to compare antimicrobial activity and surface interactions of naked IONPs, amino-functionalized NPs (NP-APTES), and nanoconjugated teicoplanin (NP-TEICO) with non-conjugated teicoplanin. As bacterial models, differently resistant strains of three Gram-positive bacteria (Staphylococcus aureus, Enterococcus faecalis, and Bacillus subtilis) and a Gram-negative representative (Escherichia coli) were used. The results indicated that teicoplanin conjugation conferred a valuable and prolonged antimicrobial activity to IONPs toward Gram-positive bacteria. No antimicrobial activity was detected using NP-TEICO toward the Gram-negative E. coli. Although IONPs and NP-APTES showed only insignificant antimicrobial activity in comparison to NP-TEICO, our data indicate that they might establish diverse interaction patterns at bacterial surfaces. Sensitivity of bacteria to NPs varied according to the surface provided by the bacteria and it was species specific. In addition, conjugation of teicoplanin improved the cytocompatibility of IONPs toward two human cell lines. Finally, NP-TEICO inhibited the formation of S. aureus biofilm, conserving the activity of non-conjugated teicoplanin versus planktonic cells and improving it toward adherent cells.